2019
DOI: 10.1109/access.2019.2943479
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Behavior of Fiber Reinforced Cemented Tailings Backfill Under Three-Point Bending

Abstract: Mining methods use cemented tailings backfill (CTB) for filling mined-out voids and make operations safer since employees are working under it. Hence, the durability behavior of CTB is of great importance in applications, for example, in the assessment of slope stability when extracting ore left in neighboring stopes. Addition of cement content would increase the strength of CTB but creates extra costs to mines. To cut cement-related costs as well as improve durability, different types of fibers are added to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(12 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Thus, exploring the feasibility of using FA and DG to prepare mine backfilling is the main purpose of this study. Scholars have so far used backfill samples with ecofriendly binders [30,31] and cement-based composites [32] on a single or combination of FA [33,34] and DG [35,36] as industrial waste.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, exploring the feasibility of using FA and DG to prepare mine backfilling is the main purpose of this study. Scholars have so far used backfill samples with ecofriendly binders [30,31] and cement-based composites [32] on a single or combination of FA [33,34] and DG [35,36] as industrial waste.…”
Section: Introductionmentioning
confidence: 99%
“…Zain et al [ 4 ] showed that the STS/CS ratio decreases as the strength class of concrete is upgraded, therefore, high strength PCCs are more vulnerable to brittle failure than normal strength PCCs. PCC has low energy absorption capacity (or toughness) under both tensile and compressive loadings [ 5 , 6 ]. It undergoes a sudden failure after carrying the load beyond its peak capacity and it has very low residual strength (almost negligible compared to fiber-reinforced concrete) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since these are mixtures of crushed rocks and mill processing fluids, washing machines or concentration left over after the extraction of metals, minerals, mineral fuels, or economic coal from the mining resource [6]. Another definition is that tailings are fine-grained, particulate solids consisting of ground rock slurry, water, and chemical residues that remain after the minerals or commercial elements have been removed from the ore [7]. Thus, mine tailings and associated accidents have been identified as one of the most dangerous environmental problems worldwide [8].…”
Section: Introductionmentioning
confidence: 99%